Science Communication activities and Trust amongst Nigerian scientists and journalists - Weitkamp, Emma; Larbey, Ruth; Maina, Mahmoud, Bukar; Petherick, Katy; Muhammad, Mustapha; Tsanni, Abdullahi; Hong, Xinyang; Al-Gazali, Abdulhamid (My University, 2022)
Relatively few studies have explored the communication practices of researchers and journalists working in African contexts. We set out to explore the communication activities undertaken by Nigerian health researchers and journalists, their motivations and the barriers they face in communicating about health topics with lay audiences, as well as their trust in a range of sources of scientific information. The study adopted a survey methodology, recruiting 69 participants at a communications training workshop for both health researchers and journalists. We found high levels of participation in research communication amongst health researchers compared with previous work. While many barriers are similar to those faced by researchers in other contexts, our respondents highlighted that lack of support from managers is a significant hurdle, which has not been highlighted in other studies. Both journalists and researchers primarily communicate science with the aim of educating, informing, entertaining or inspiring their audiences. Regarding trust, both researchers and journalists broadly trust sources linked to science, such as academic journals. However, trust in industry, NGOs and other media was higher amongst journalists than health researchers. Least trust was invested in social media sources, with the exception of material posted on accounts linked to universities.
Keywords: Health communication; Journalists; Researchers; Science Communication; Trust